Solomon, a Sacred Oratorio In Score - Handel, George Frideric 1685-1759; Mendez, Moses 1690?-1758 (London Arnold, 1790)
'Solomon' is based on the biblical stories of the wise king Solomon from the First Book of Kings and the Second Book of Chronicles, with additional material from Antiquities of the Jews by ancient historian Flavius Josephus. The music was composed between 5 May and 13 June 1748, and the first performance took place on 17 March 1749, with Caterina Galli in the title role at the Covent Garden Theatre in London, where it had two further performances. Handel revived the work in 1759.
Minor annotations in pencil (crosses, corrections in the accidentals, and additions in the figured bass) at pages 51-53, 77, 89, 90, 96, 119, 133, 244, 265, 267, 268, 309, and 315; in ink at pages 71, 248, 283, 285, and 288
Ex Libris William Pole Birmingham (plate and manuscript on title page)
Leather binding with marbled-paper front and back, heavily restored
With all the additional Alterations, Composed in the Year 1749
Keywords: Solomon -- King -- 989-931 BC; Theatre Royal, Covent Garden (London, United Kingdom); 18th Century (1701-1800); Oratorio; Old Testament; United Kingdom